Efficiency of Renewable Energy Plants in Russia - An, Jaehyung; Gudmundsson, Fe Amor Parel; Sokolinskaya, Natalia; Prosekov, Sergey; Meynkhard, Artur; Arnórsson, Auðunn; Simonyan, Lernui (International Journal of Energy Economics and Policy, 2020)
The article offers an evaluation of the efficiency of power plants that use renewable energy. With the way tariffs for thermal energy are nowadays, the minimum cost of solar water heating (SWH) plants with a payback period of 7 years should not exceed $50 per square meter. Capital expenses for SWH plants with a drain-down system are 1,4-1,6 times lower than traditional SWHs with circulation systems, and their payback period does not exceed 5-5,7 years. Based on the present electricity tariffs in Russia, it is estimated that the minimal acceptable investments in wind turbines with a payback period of 7 years should not exceed $800/kW. Biogas that is obtained from specialized plants of medium and high-power costs $15,000-60,000 per cubic meter. But the price of biogas produced in low energy power plants is about $80,000-270,000, which is cheaper than natural gas. So, the use of biogas is economically justified at the moment. Keywords: solar water heating plants, wind turbines, biogas plants, thermal energy, electrical energy, cost of plants JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8786